Practice of Informed Consent, Confidentiality and Privacy by Physicians at a Tertiary Care Teaching Hospital - Rafique, Zoheb Rafique; Bhatti, Urooj (Bangladesh Journal of Bioethics, 2015)
Objective: The aim of this paper was to assess the practice of medical ethics by the physicians at a public sector hospital in Jamshoro Sindh. Material and methods: This survey was conducted at four medical units of tertiary care hospital at jamshoro in the month of august 2014. Participants were randomly selected from patients aged over 18 years. A structured questionnaire was designed and the participants were asked about their demographic profile and their physicians practice regarding informed consent, maintaining confidentiality, privacy and other treatment formalities. Written consent was taken from all the participants before interview. Results: A total of 100 patients were randomly selected for this study. The majority of patients reported that informed consent was taken from them. The patients also responded that privacy and confidentiality is maintained during their treatment. However, many patients agreed that they were not properly informed about the laboratory findings, role of proposed drugs and also side effects of drugs. Conclusion: There is marked improvement in the practice of medical ethics by physicians of this tertiary care hospital. However, awareness workshops should be conducted to update and improve the knowledge of medical ethics among physicians. This will surely help them translate the knowledge into practice. DOI: http://dx.doi.org/10.3329/bioethics.v5i3.21531 Bangladesh Journal of Bioethics 2014 Vol.5 (3): 1-5.